High-performance protonic ceramic fuel cell cathode using protophilic mixed ion and electron conducting material. Issue 5 (12th January 2022) - Hu, Dingyue; Kim, Junyoung; Niu, Hongjun; Daniels, Luke M.; Manning, Troy D.; Chen, Ruiyong; Liu, Bowen; Feetham, Richard; Claridge, John B.; Rosseinsky, Matthew J.
Abstract : High-performance and stability for protonic ceramic fuel cell cathode applications are realised in a self-assembled nanocomposite material Ba0.5 Sr0.5 (Co0.7 Fe0.3 )0.6875 W0.3125 O3− δ (BSCFW) through interplay of single and double perovskite phases. Abstract : Protonic ceramic fuel cells (PCFCs) are attractive energy conversion devices for intermediate-temperature operation (400–600 °C), however widespread application of PCFCs relies on the development of new high-performance electrode materials. Here we report the electrochemical and protonic properties of a self-assembled nanocomposite, Ba0.5 Sr0.5 (Co0.7 Fe0.3 )0.6875 W0.3125 O3− δ (BSCFW) consisting of a disordered single perovskite and an ordered double perovskite phase, as a PCFC cathode material. BSCFW shows thermodynamic and kinetic protonic behaviour conducive to PCFC application with favourable proton defect formation enthalpy (Δ H = −35 ± 7 kJ mol −1 ) comparable to existing proton conducting electrolyte materials. BSCFW presents an excellent polarization resistance ( R p ) of 0.172(2) Ω cm 2 at 600 °C and a high power density of 582(1) mW cm −2 through single-cell measurement, which is a comparable performance to current state-of-the-art cathode materials. BSCFW exhibits good chemical and thermal stability against BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3− δ (BZCYYb) electrolyte with a low R p degradation rate of 1.0(1) × 10 −6 Ω cm 2 min −1 . These performance and stability figures represent an advance beyond those of Ba0.5 Sr0.5 Co0.7 Fe0.3 O3− δ (BSCF), which is unstable under the same conditions and is incompatible with the electrolyte material. Our comprehensive characterization of the protonic properties of BSCFW, whose performance and stability are ensured via the interplay of the single and double perovskite phases, provides fundamental understanding that will inform the future design of high-performance PCFC cathodes.